L’ethnocritique de la littérature : Présentation et situation - Marie Scarpa (Multilinguales)
This article situates the ethnocriticism of literature first of all in the perspective of the complex relations between literature and anthropology, then from the point of view of its proximity to other closely-related critical fields. It also proposes an updated definition of this new method of literary analysis, its objectives and themes (notably the homology between ritual and narrative, the complex interactions between forms of orality and literacy, the question of liminal characters).